The influence of sleep deprivation on the cognitive processes in medical students during exam session - Anna Janocha; Aldona Molęda; Tadeusz Sebzda (Nofer Institute of Occupational Medicine, 2023)
Background Along with socio-economic pression increase in developed countries, the progressive shortening of night sleep has been observed. Sleep plays a vital role in human organism regeneration, and its deprivation leads to a series of adverse psychosomatic effects, including intellectual performance limitation or reducing body immunity, which increases susceptibility to diseases. Chronic sleep deprivation, quite often affecting medical students, significantly contributes to hypersomnia and leads to chronic fatigue. Material and Methods The results of 60 students were analysed; students were divided into 2 subgroups, depending on the average sleep duration during previous 2-3 nights: IA (2.3±0.8 h on average) and IB (4.9±0.5 h on average). The control group consisted of 50 students, whose night sleep duration in that period was 7.5±0.62 h. In all subjects under analysis visual and auditory evoked potentials were registered, which is a non-invasive method of cognitive performance tests. Results The obtained results showed that people with average night sleep duration 2.3±0.8 h (subgroup IA) had worse rate and precision of stimulus response, and thereby significantly worse (p < 0.001) sensorimotor performance, then those from subgroup IB. The study of evoked potentials showed significant (from p < 0.04 to p < 0.001) elongation of all latency p-waves connected with the stimulus perception (N 75 ) and attention span (P 100 , N 135 ). Moreover, significant elongation of visual latency wave P 100 and auditory wave V was related to psychophysical fatigue occurring in sleep deprivation. Conclusions The analysis of this study results, obtained in medical students showed that sleep deprivation occurring during exam session is closely related to cognitive abilities, which in turn adversely affects the academic achievement. These results indicate that night sleep duration is a differentiating factor for cognitive abilities quality. Also, psychosomatic fatigue adversely affects cognitive processes. Med Pr. 2023;74(1):27-40